Severity of Obstruction Associated with Pulmonary Hypertension in COPD Patients at Arifin Achmad General Hospital: What Factors Influence? - Edra, Alven; Syamsu, Adrianison; Siswanti, Dyah (Indonesian Society of Respirology (ISR), 2025)
Background: Pulmonary hypertension can occur in stable chronic obstructive pulmonary disease (COPD) patients despite its unknown etiology or as a complication associated with other processes. Pulmonary hypertension was divided into five broad categories, including processes with common pathogenic mechanisms. The true incidence of pulmonary hypertension in COPD is unknown, as no systematically performed screening method can be widely used in COPD patients, while the mortality rate or complications from COPD are still very high. Method: This study method was a cross-sectional study. This study was conducted on stable COPD patients who came to the pulmonary department at Arifin Achmad General Hospital to assess its association with the risk of pulmonary hypertension. Results: This study involved 77 research subjects with the highest age <65 years (64.9%) with male gender (84.4%), airflow limitation degree GOLD II (moderate) (50.6%), severe Brinkman Index (76.6%), comorbid hypertension (7.8%), Asymmetric Dimethylarginine (ADMA)0 inflammatory marker including low-risk category (77.9%) and mild echocardiographic interpretation (75.3%). The Association of COPD severity was significant to the risk of pulmonary hypertension, the degree of airflow limitation (P=0.0001) and echocardiography interpretation (P=0.0001). At the same time, there was no significant association with ADMA levels (P=0.239). The Brinkman Index of smokers (P=0.006) was an important risk factor for pulmonary hypertension. Conclusion: There was an association between COPD severity, echocardiographic interpretation and smoking status based on the Brinkman Index and the risk of pulmonary hypertension.